Combining ability of selected soybean [Glycine max (L.) Merrill] parental lines - Otusanya, G.O.; Chigeza, G.; Chander, S.; Abebe, A.T.; Sobowale, O.O.; Ojo, D.K.; Akoroda, M. (Agricultural Research Communication Center, 2022)
Background: The success of hybridization programme depends on the combining ability of parental lines. Methods: Seven soybean genotypes and all their partial diallel crosses in the F2 generation were evaluated in a randomized complete block design at two locations in Nigeria, during the 2017-2018 growing season. Result: Analysis of variance showed that both environments and genotypes were significantly different for all measured traits. The genotype TGx 1988-5F was the best general combiner for earliness in flowering and poding, while TGx 1448-2E was the best general combiner for number of pods/plant and seed yield/plant. Crosses having significant and positive specific combining ability effect for number of pods/plant and seed yield/plant were TGx 1485-1D × TGx 1448-2E and TGx 1988-5F × TGx 1989-19F, respectively. Genotypes TGx 1988-5F and TGx 1448-2E exhibiting good general combining ability for earliness and seed yield/plant, are thus, promising for utilization in the future hybridization programme for soybean improvement.